2011
DOI: 10.4103/0253-7613.83109
|View full text |Cite
|
Sign up to set email alerts
|

Managing diabetic ketoacidosis in non-intensive care unit setting: Role of insulin analogs

Abstract: Aim:To compare the efficacy and safety of rapid acting insulin analog lispro given subcutaneously with that of standard low-dose intravenous regular insulin infusion protocolin patients with mild to moderate diabetic ketoacidosis.Materials and Methods:In this prospective, randomized and open trial, 50 consecutive patients of mild to moderate diabetic ketoacidosis were randomly assigned to two groups. The patients in group 1 were treated with intravenous regular insulin infusion and admitted in intensive care u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 20 publications
1
34
0
3
Order By: Relevance
“…76 Potential candidate patients include those who are alert and do not otherwise need admission to a critical care area, have a pH above 7.0, and bicarbonate of at least 10 mmol/L (≥10 mEq/L) 77. Four prospective randomized studies in adult patients with diabetic ketoacidosis compared subcutaneous rapid acting insulin (initial bolus of 0.3 units/kg followed by 0.1-0.2 units/kg every 1-2 hours) with conventional diabetic ketoacidosis treatment and found no difference in patient outcomes 77787980. With subcutaneous insulin regimens, administration of intravenous fluids and electrolytes, as well as monitoring, is identical to what is recommended with intravenous insulin therapy.…”
Section: Acute Managementmentioning
confidence: 99%
“…76 Potential candidate patients include those who are alert and do not otherwise need admission to a critical care area, have a pH above 7.0, and bicarbonate of at least 10 mmol/L (≥10 mEq/L) 77. Four prospective randomized studies in adult patients with diabetic ketoacidosis compared subcutaneous rapid acting insulin (initial bolus of 0.3 units/kg followed by 0.1-0.2 units/kg every 1-2 hours) with conventional diabetic ketoacidosis treatment and found no difference in patient outcomes 77787980. With subcutaneous insulin regimens, administration of intravenous fluids and electrolytes, as well as monitoring, is identical to what is recommended with intravenous insulin therapy.…”
Section: Acute Managementmentioning
confidence: 99%
“…In a prospective, randomized clinical trial in India, Karoli and coworkers reported that once the DKA patient is evaluated in the ED, and categorized in the severity score, direct admission to a regular ward provided no additional mortality and the only complication noted was hypoglycemia. Other groups have used other classifications to allocate resources for patients with DKA[ 15 ]. In a retrospective study, Marinac and Mesa, using laboratory criteria (serum bicarbonate, anion gap, base excess and serum osmolality), and diastolic blood pressure, patients were grouped in 5 grades (Grade 0 - IV)[ 19 ].…”
Section: Is Dka a Criterion For Icu Admission?mentioning
confidence: 99%
“…7 For this reason, IV infusion of regular insulin has been the mainstay of treatment of DKA as it causes a more predictable fall in blood glucose and it allows for rapid adjustments. 8 Insulin lispro is a genetically engineered analogue of human insulin in which proline at position B28 and lysine at position B29 are inverted in their sequence reducing the formation of insulin dimers and hexamers. This structural change ensures more rapid absorption and elimination from the subcutaneous injection site, resulting in the rapid onset and a short duration of hypoglycaemic activity.…”
mentioning
confidence: 99%